Understanding consumer economic nationalism: construction and validation of the CENTSCALE - Cheah, Isaac; Phau, Ian (School of Marketing, Curtin Business School, 2008)
Economic nationalism has been identified as a critical component of nationalistic sentiment, influencing cognitions, attitudes, evaluation and purchase intentions. While a distinction is made between economic nationalism and other measures of national and international orientation (ie. consumer ethnocentrism), previous empirical studies explore the concept in a ?unified? form. This study bridges this gap by developing a scale specifically tailored to measure consumer economic nationalistic tendencies. Scale generation, purification, validation and confirmation are achieved through five studies.